2016
DOI: 10.1089/jamp.2015.1210
|View full text |Cite
|
Sign up to set email alerts
|

Btk Inhibitor RN983 Delivered by Dry Powder Nose-only Aerosol Inhalation Inhibits Bronchoconstriction and Pulmonary Inflammation in the Ovalbumin Allergic Mouse Model of Asthma

Abstract: Background: In allergen-induced asthma, activated mast cells start the lung inflammatory process with degranulation, cytokine synthesis, and mediator release. Bruton's tyrosine kinase (Btk) activity is required for the mast cell activation during IgE-mediated secretion. Methods: This study characterized a novel inhaled Btk inhibitor RN983 in vitro and in ovalbumin allergic mouse models of the early (EAR) and late (LAR) asthmatic response. Results: RN983 potently, selectively, and reversibly inhibited the Btk e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Previous studies on the genome-wide gene expression profile of CRSwNP showed increased ALOX5AP gene expression levels in the nasal polyps of patients with aspirin-intolerant asthma (Sekigawa et al, 2009 ) and decreased methylation levels of ALOX5AP in a genome-wide methylation profile of nasal polyps (Cheong et al, 2011 ). BTK, a member of the Tec family of tyrosine kinases, has been indicated to play crucial roles in B cell development and signal transduction downstream of the high-affinity receptor for IgE (FcεR) on mast cells and basophils in an ovalbumin-induced mouse model of asthma (Phillips et al, 2016 ). However, there have been no studies on BTK in chronic nasal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the genome-wide gene expression profile of CRSwNP showed increased ALOX5AP gene expression levels in the nasal polyps of patients with aspirin-intolerant asthma (Sekigawa et al, 2009 ) and decreased methylation levels of ALOX5AP in a genome-wide methylation profile of nasal polyps (Cheong et al, 2011 ). BTK, a member of the Tec family of tyrosine kinases, has been indicated to play crucial roles in B cell development and signal transduction downstream of the high-affinity receptor for IgE (FcεR) on mast cells and basophils in an ovalbumin-induced mouse model of asthma (Phillips et al, 2016 ). However, there have been no studies on BTK in chronic nasal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, immune dysfunction and abnormal expression of inflammation factors are closely associated with capillary bronchial asthma, bronchitis and other infant asthmatic diseases (28)(29)(30). Notably, Li et al (31) have demonstrated that the PKA-dependent NF-κB signaling pathway is a novel target for drug action in asthma therapy.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to prevent influenza-induced acute lung injury through reduction of pro-inflammatory mediators [52]. Btk inhibitor RN983 showed much more anti-inflammatory potency than corticosteroid budesonide in mouse lung in form of inhalation [53]. This makes it effective in the treatment of allergic asthma.…”
Section: Potential Mechanisms Of Respiratory Manifestations In Xlamentioning
confidence: 99%